ANALISIS HASIL INVESTASI, PENDAPATAN PREMI, DAN BEBAN KLAIM TERHADAP LABA PERUSAHAAN PERASURANSIAN DI INDONESIA - Sofyan Marwansyah; Ambar Novi Utami (Politeknik Negeri Batam, 2017)
Insurance is a fund raising agency sourced from the receipt of insurance premiums from the public and distributed by claims. In addition to premium receipts, the company also puts its funds in the form of investments. This aims of this paper is to analyze the investment returns, premium income, and claims expense to profit using partial correlation, determination and multiple linear regression. The methods that use to collects the data for this final task are using observation and study documentation using quantitative analysis. Analytical technique is multiple linear regression using IBM SPSS 21 software. The used data in this paper is secondary data that obtained from the website of Otoritas Jasa Keuangan. From the results of the correlation coefficient test partially obtained investment returns and premium income has a significant relationship to profit, a positive value of 0.657 and 0.737 means the relationship is strong and unidirectional whereas, claims load has a significant relationship to profit, negative value of -0.786 means strong relationship And counterclockwise, simultaneously (together) shows that investment returns, premium income, claims expenses have significant relationship to profit, and a positive value of 0.881. The result of determination coefficient test shows that there is a significant influence of 77.6% and the remaining 22.4% influenced by other factors. The regression equation formed is Y = -2,682 + + – 2,369 + e.